Thermal stability of the nanostructure of mechanically milled Cu–5 vol% Al2O3 nanocomposite powder particles. Issue 8 (1st May 2014) - Zhou, Dengshan; Zhang, Deliang; Kong, Charlie; Munroe, Paul; Torrens, Rob
Abstract